The Novice English Teachers' Experience: Practices and Challenges - Septiani, Ani; Emiliasari, Raynesa Noor; Rofi'i, Agus (Academic Journal PERSPECTIVE: Education, Language, and Literature, 2019)
The aims of this research are to reveal teaching practices of novice English teachers and the challenges faced by novice English teachers. This is a narrative qualitative. The researcher employs observation and interview as the research instrument. The result of this research reveals the way of teaching practices of novice English teachers still not maximal, they faced several challenges related with teaching practices and with the school environment in terms of in the beginning the novice English teachers feel lack of ability, difficult in arrange and implementing the lesson plan, motivating the students, the alteration of emotion, interactions with colleagues, the parents of the students and with the students, time management is the main challenges in the boarding school, the teachers cannot implement time management with maximal.